Measurement of Radon-222 Concentration in Soil Samples of some Sulfuric Spring in Hit City Using CR-39 Detector - Baghdad Science Journal (مجلة بغداد للعلوم)
In this study, concentrations of radon were measured for seventeen samples of soil distributed in three Sulphuric Spring, in addition to other regions as a background in Hit City in AL-Anbar Governorate. The radon concentrations in soil samples measured by using alpha-emitters registration that emits from radon (222Rn) in (CR-39) track detector. The concentrations values were calculated by a comparison with standard samples. The results show that the radon concentrations in first spring varies from (258.253- 347.762 Bq/m3), second spring (230.374-305.209 Bq/m3), third spring (292.002-336.023 Bq/m3) and the average radon concentration in other regions (187.821 Bq/m3). As a conclusion of the study radon concentration in Sulphuric Spring is relatively higher than the background.